Print to fit : the New York Times, Zionism and Israel, 1896-2016 - Auerbach, Jerold S. (Antisemitism in America., 2019)
Ever since Adolph Ochs purchased The New York Times in 1896, its enduring masthead motto - ""All The News That's Fit To Print""--Has become news that fits Times' discomfort with the idea, and since 1948 the reality, of a thriving democratic Jewish state in the historic homeland of the Jewish people.